ANALISIS PELAYANAN PEMBUATAN NOMOR INDUK BERUSAHA (NIB) UNTUK KESADARAN LEGALITAS USAHA BAGI UMKM DI KELURAHAN KAMPUNG RAWA KECAMATAN JOHAR BARU JAKARTA PUSATTAHUN 2022 - Alifa Tasya Permata; Yoka Mai Patria (Jurnal Ilmu Administrasi Publik, 2025)
This research is based on the results of observations made in kampung rawa village and found a problem that is not thorough socialization, lack of access to information to business actors about the manufacture of NIB, so there are still many business actors who do not know what NIB and the benefits derived from the manufacture of NIB. The need for improvement of existing systems in OSS on complaints experienced by business actors. The purpose of this study was to determine the analysis of the service of making a business identification number and awareness of business actors about the legality of their business, what factors are obstacles and efforts made to overcome obstacles in making a business identification number. This type of research is qualitative research with descriptive case studies. This research approach uses fitzsimmons theory on aspects of Service. The results showed that the analysis of the service of making the identification number seeks to awareness of the legality of the business for MSMEs is good enough with the facilities and infrastructure provided by the village. However, there are still problems such as lack of awareness of business actors about the importance of making NIB and ignorance of business actors in making business identification numbers, while the OSS is still not user friendly with the current technology system. Making a business license now like NIB is easier but because people lack awareness of knowledge about the business license there are still those who have not registered NIB. Keywords Service Analysis, Business legality, NIB, MSME